(untitled) (Research, Society and Development, 2022)
Objetive: to analyze research priorities in Brazil, specifically related to the mental health of the Brazilian population. Method: This is a descriptive study on the profile of research on mental health related to Covid-19, based on the observatory of research with human beings registered on the Brazil platform (OPB). The data used were extracted from the public domain observatory, using the time frame corresponding to the months of March to December 2020 and the keyword Mental Health. Descriptive analysis was performed based on the number of projects per region, federative units, type of study, proposing institution (public/private), sample size. Results: Of the total of 788 protocols approved by CONEP on Covid-19, 86 (10.9%) are studies on mental health. The Southeast represents the largest number of projects, followed by the South region. The studies have different methodological characteristics, in addition to great variability in the number of participants, which ranged from 20 (qualitative study) to 129,134 participants. Diversity in the topics covered was also observed. Public institutions lead the studies (79), with the University of São Paulo having the largest number of projects. Conclusion: We sought to know and analyze the research data inserted in the platform, in order to disseminate research scenarios involving human beings in Brazil.